Gaining access in an ethnography with children in open public spaces: confidence dilemmas in times of risk - Ivana Martins da Rosa; Manuela Ferreira (Universidade Federal de Santa Catarina, 2019)
Ethnography with children generates permanently ethical-methodological dilemmas, which require the researcher to adopt a methodological reflexivity posture about the events experienced and negotiated in the fieldwork. Focusing on the construction of relationship with children between 6 and 10 years old in the public open spaces of a fishing community in the north of Portugal this paper reflects on the processes of gaining access to their cultural worlds and emerging dilemmas around confidence regarding to: i) the identity of the ethnographer; ii) the limits and consequences of confidences intertwined among children and ethnographer. It is understood that such dilemmas are heightened in the context in which ethnography occurs, in the sense that they incorporate some of the social complexities that affect childhood experiences in contemporary Western societies, interpreted as "societies of risk."